Categorizing sources of risk and the estimated magnitude of risk - Aragonés, Juan Ignacio; Moyano, Emilio; Talayero, Fernando (The Spanish Journal of Psychology, 2008)
The social perception of risk is considered a multidimensional task, yet little attention has been paid to the cognitive components that organize sources of risk, despite their having been discovered in various research studies. This study attempts to concretely analyze the cultural dimension involved in those processes. In the first phase, we tried to discover to what extent sources of risk are organized into the same categories by people from different countries. In order to do so, two groups of participants were formed: 60 Spanish psychology students and 60 Chilean psychology students classified 43 sources of risk into different groups according to the criteria they found appropriate. The two samples classified risk into identical groups: acts of violence, drugs, electricity and home appliances, household chemicals, chemicals in the environment, public construction projects, transportation, sports, and natural disasters. In a second study, 100 Spanish and 84 Chilean students were asked to evaluate the magnitude of the damage incurred by 17 sources of risk. In both groups, it was observed that the evaluation of damage resulting from each source of risk was affected by its category.